The Risk of Immune-Related Thyroid Dysfunction Induced by PD-1/PD-L1 Inhibitors in Cancer Patients: An Updated Systematic Review and Meta-Analysis - Tian, Yuan; Li, Ran; Liu, Yan; Li, Meng; Song, Yuxiao; Zheng, Yan; Gao, Aiqin; Wen, Qing; Su, Guohai; Sun, Yuping (Frontiers in Oncology, 2021)
Background: Thyroid dysfunction is common for cancer patients receiving PD-1/PD-L1 inhibitor therapies. To clarify the incidence risk of thyroid dysfunction would be important for guiding PD-1/PD-L1 related immunotherapy. Therefore, the updated meta-analysis was conducted to evaluate the risk of thyroid dysfunction caused by PD-1/PD-L1inhibitors. Methods: PD-1/PD-L1 inhibitor related clinical trials were collected by a systematic search of the PubMed. Some relevant studies were identified by a manual search. The incidence risk of all grades and grades 3-5 was analyzed and evaluated by random effect model. The Newcastle Ottawa Scale was used for the quality assessment for all enrolled trials. Results Forty-three clinical trials were identified. Compared with chemotherapy, the risk of hypothyroidism for all grades in PD-1/PD-L1 group was significantly higher (OR=7.15, 95%CI:[4.85, 10.55], I2=40%, Z=9.91(P <0.00001)) than that of the control group. Similar results could also be noted, when the control group was placebo or CTLA-4. When PD-1/PD-L1 was combined with other treatments for cancer patients, the risk of hypothyroidism of all grades was also significantly increased. Similar to the analysis results of hypothyroidism, PD-1/PD-L1 inhibitors played the same role in increasing the risk of hyperthyroidism and thyroiditis. Few significant analysis results was noted, when the risk of thyroid dysfunction of grades 3-5 was evaluated. Conclusion Whether used alone or in combination with other anti-tumor drugs, PD-1/PD-L1 inhibitors increased the risk of thyroid dysfunction, especially for hypothyroidism. In addition, PD-1/PD-L1 had advantages over chemotherapy and CTLA-4 in increasing the risk of thyroid dysfunction.